PREVALENCE OF FRAILTY IN CHINESE OLDER PEOPLE: A CROSS-CULTURAL STUDY - Yu, R. (Innov Aging, 2017)
Methods: Data were derived from two population-based studies, the Mr Os and Ms Os (Hong Kong) studies (n=4000) and the Taiwan Longitudinal Study on Aging (TISA, n=2653). Older people aged 65 years and older living in the community were invited to respond to a structured questionnaire. Frailty Index (FI) was constructed from 36 variables covering medical and drug histories, geriatric syndromes, assessment of physical and cognitive functioning, psychological wellbeing, and nutritional status. Frailty was defined as the index ≥ 0.25. The ratio of FI to life expectancy at birth (LE) was used as an indicator of compression of morbidity. Results: The weighted average prevalence rate of frailty was 41.8% and the rates were more prevalent in Taiwan urban and Taiwan rural areas (40.5% and 42.7% respectively) compared to Hong Kong (15.2%, P<0.05). Frailty increased with age: 65–74 years 9.6%-30.4%; 75–84 years 19.4%-48.8%; older than 85 years 24.7%-77.0% (P<0.05). Prevalence of frailty were statistically higher in women (ranged from 21.1%-54.3%) than in men (ranged from 9.4%-31.7%, P<0.05) and the differences were found in all age groups (P<0.05). The ratios of FI/LE were higher in Taiwan urban and Taiwan rural areas (both 0.25) compared to Hong Kong (0.17, P<0.05). Conclusion: This comparison provides better understanding of levels in the health of older people and provides useful data to inform government policies. Further analyses are needed to compare the role of personal, environmental, and health and social care systems in contributing to frailty across the study populations.